2021
DOI: 10.1101/2021.05.25.445633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sorghum Root Epigenetic Landscape During Limiting Phosphorus Conditions

Abstract: Efficient acquisition and use of available phosphorus from the soil is crucial for plant growth, development, and yield. With an ever-increasing acreage of croplands with suboptimal available soil phosphorus, genetic improvement of sorghum germplasm for enhanced phosphorus acquisition from soil is crucial to increasing agricultural output and reducing inputs, while confronted with a growing world population and uncertain climate. Sorghum bicolor is a globally important commodity for food, fodder, and forage. K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Some studies have also found that the environment can induce changes in methylation. For example, a study on root system architecture found methylation variation associated with environmental stresses [ 108 ]; other studies have found that DNA methylome is stable under stresses [ 94 ].…”
Section: Opportunities and Challenges For Crop Improvementmentioning
confidence: 99%
“…Some studies have also found that the environment can induce changes in methylation. For example, a study on root system architecture found methylation variation associated with environmental stresses [ 108 ]; other studies have found that DNA methylome is stable under stresses [ 94 ].…”
Section: Opportunities and Challenges For Crop Improvementmentioning
confidence: 99%
“…51 The novel's apocalyptic ending ("I see them now, I see the fires") 52 appears to relate as much to the narrative and syntactical scaffolding-"how words are ordered to create meaning, how moving through that order is a kind of unfolding"-as to a geopolitical environment that we are invited to read as allegorical, but which is grounded in untranslatability. 53 Gladman's novels posit a relationship-or what I earlier called a zone of translation-between the crumbling (or "migrating") buildings and the creation of fiction. 54 It is as if they literalized Walter Benjamin's idea: "Allegories are, in the realm of thoughts, what ruins are in the realm of things."…”
Section: World-ecology and The Text In Crisismentioning
confidence: 99%